Deforestation and child diet diversity: a geospatial analysis of 15 sub-Saharan African countries. (April 2017) - Jones, Andrew D; Acharya, Yubraj; Galway, Lindsay P
Abstract: Background: Rapid deforestation worldwide could have important consequences for human nutrition in view of the numerous ecosystem services associated with landscape biodiversity. In this study, we aimed to examine the association between deforestation in sub-Saharan Africa and diet diversity among children aged 6–24 months. Methods: We used geolocated Demographic and Health Survey (DHS) dietary data from 2011–15 for 28 354 children from 6187 DHS enumeration clusters in 15 countries of sub-Saharan Africa. Child diet diversity was modelled as a 7-item continuous score and as a dichotomous variable based on WHO cut-offs for assessing minimally diverse child diets. Deforestation, defined as a stand-replacement disturbance or change to non-forest state, was measured using loss of forest cover based on a time series analysis of USGS/NASA Landsat imagery between 2000 and 2012. Deforestation and DHS survey data were linked using a Geographic Information System. Multiple regression models for all countries combined and for distinct regions were analysed using OLS and logit specifications, with adjustment for potentially confounding covariates. Findings: Loss of forest cover was negatively associated with child diet diversity score (adjusted β coefficient–0·899 [95% CI −1·515 to −0·283]; p=0·004), as well as recent consumption of legumes (odds ratio 0·038 [95% CI 0·008 to 0·183]; p<0·0001) and flesh foods (0·205 [0·079 to 0·527]; p=0·001). These trends were strongest in the west sub-Saharan Africa region. Deforestation also showed a negative association with minimum diet diversity (odds ratio 0·271 [95% CI 0·069 to 1·068]; p=0·062) and recent consumption of all other food groups, with the exception of staple foods; however, these trends were consistent with random variation. Deforestation in 15 countries of sub-Saharan Africa was associated with lower diet diversity among young children. Interpretation: This hypothesis-generating research provides support for future controlled studies that examine pathways linking regional environmental change and human nutrition. Funding: None.